Tributalizmo koncepcija: S. Amino, J. Haldono ir H. H. Stahlio sampratų lyginamoji analizė - Babinskas, Nerijus (Lietuvos istorijos studijos, 2009)
By this article, the author wants to revive discussion about Marxist schemas of social development and their applicability for constructing models of universal history. There are attitudes of three scholars presented in the current text: Samir Amin, who is known in the Western historiographical tradition as a main creator and promoter of the concept of the tributary mode of production; John Haldon, who paid quite much attention to the mentioned concept and dedicated his entire book to this issue; and Henri H. Stahl, who created an original alternative approach to the issue of tributalism. The author rejects J. Haldon’s concept of mode of production as too narrow (in fact, J. Haldon identifies mode of production with mode of exploitation). The author proposes a wider definition of mode of production, which is based on the analysis of Karl Marx’s texts. According to the author, the most important elements of mode of production are the exploitative subject (it is defined by property of conditions of production, which realizes as a social power) and productive/obligatory unit, which can be manifested as a household of an individual direct producer or as a community. The author proposes the following principled classification based on his conception of mode of production: • A proprietor of land is a monarch/state, and a productive/obligatory unit is a community (of Asiatic/Slavonic type); • A proprietor of land is a monarch/state, and a productive/obligatory unit is a household of an individual direct producer; • Proprietors of land are private landowners, and a productive/obligatory unit is a community (of Asiatic/Slavonic type); • Proprietors of land are private landowners, and a productive/obligatory unit is a household of an individual direct producer. The most important conclusions of the author’s are as follows: • H. H. Stahl’s statement that there were alternatives in the social development of precapitalist societies is definitely reasonable. • Keeping in mind controversies among the presented conceptions of tributalism, the author emphasizes that, at the moment, the question of the typology of antagonistic precapitalist societies remains open; so further researches and discussions are necessary. • As a point of departure for further researches and discussions the author proposes his principled classification of antagonistic precapitalist societies based on criteria of an exploitative subject and a productive / obligatory unit.